NILAI-NILAI SOSIAL DALAM CERPEN UJIAN TABIB KARYA LINDA CHRISTANTY DAN RELEVANSINYA SEBAGAI BAHAN AJAR BAHASA INDONESIA DI SMA - Lariyos, Zidan; Maryam Nurlaila; Nazriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze social values in the short story Ujian Tabib by Linda Christanty using a sociology of literature approach. The research employs a descriptive qualitative method with a library research design. The data consist of textual quotations containing social values, with the primary source being the short story Ujian Tabib, published by Harian Kompas on January 3, 2026, and accessed through Kompas.id. Data collection techniques include intensive reading, contextual observation, and note-taking, while data analysis uses content analysis through stages of reduction, categorization, interpretation, and verification. The results reveal four classifications of social values: human relationships with others, human relationships with the social environment, systems of belief and social norms, and social conflict. These values are reflected through characters, events, and conflicts in the story. Furthermore, the findings can be utilized as alternative teaching material for Grade XI senior high school in the second semester, particularly in the topic “Exploring National Historical Values through Short Stories,” as they support students’ analytical skills and character development.